DETERMINATION OF LIMIT DETECTION OF THE ELEMENTS N, P, K, Si, Al, Fe, Cu, Cd, WITH FAST NEUTRON ACTIVATION USING NEUTRON GENERATOR - Sunardi Sunardi; Muryono Muryono (Universitas Gadjah Mada, 2006)
Determination of limit detection of the elements N, P, K, Si, Al, Fe, Cu, Cd, with fast neutron activation using neutron generator has been done. Samples prepared from SRM 2704, N, P, K elements from MERCK, Cu, Cd, Al from activation foil made in San Carlos, weighted and packed for certain weight then iradiated during 30 minutes with 14 MeV fast neutron using the neutron generator and then counted with gamma spectrometry (accuspec). At this research condition of neutron generator was set at current 1 mA that produced neutron flux about 5,47.107 n/cm2.s and experimental result shown that the limit detection for the elements N, P, K, Si, Al, Fe, Cu, Cd are 2,44 ppm, 1,88 ppm, 2,15 ppm, 1,44 ppm, 1,26 ppm, 1,35 ppm, 1,05 ppm, 2,99 ppm, respectively. The data indicate that the limit detection or sensitivity of appliance of neutron generator to analyze the element is very good, which is feasible to get accreditation AANC laboratory using neutron generator.